Investigating the Impact of Motivational Interviewing on Internet Addiction Among Students at Qazvin University of Medical Sciences - Kahaki , Roya; Sheikhi, Mohammad Reza; Mohammadi Zeidi , Isa; Ranjbaran, Mehdi (Iranian Journal of Neurodevelopmental Disorders, 2024)
Objective: The objective of this study was to investigate the effectiveness of motivational interviewing (MI) in reducing internet addiction among students at Qazvin University of Medical Sciences.Methods and Materials: This study employed an experimental study. A total of 108 students were randomly assigned to intervention and control group. The intervention group received six 90-minute sessions of motivational interviewing, while the control group did not receive any intervention. Data collection tools included demographical items and Internet Addiction Test (IAT) that was responded by participations at baseline, immediately after the intervention, and at a three-month follow-up. Data were entered to SPSS 25.0 and analysed by χ2, independent T-Test, and repeated measurements of ANOVA.Findings: The mean age of participants was 21.63±2.37 and 55.6% of them were female. Also, 93.5% of students were single and 78.70% of them were undergraduate. The results showed a significant reduction in internet addiction scores in the intervention group compared to the control group both immediately following the intervention and at the three-month follow-up (P